Development of Physics E-Learning with Articulate Storyline Application to Improve Science Process Skills - Sutrio, Sutrio; Gunada, I Wayan; Sumaeni, Baiq (Balai Publikasi Indonesia, 2023)
This research aims to develop physics e-learning with articulate storyline applications to improve science process skills. Researchis research and development. Development methods are 4D models with stages of define, design, development, and dissemination. The object of research is problem-based physics e-learning media with articulate storyline applications on straight-motion material. The test subjects were 20 students of grade X SMAN 1 Sikur. Data analysis techniques use qualitative and quantitative data analysis. The results of the study can be concluded that physics e-learning products with articulate storyline applications on straight-motion material are categorized as valid with an average score of 3.58, and physics e-learning is quite effective to be used to improve students' science process skills with a percentage of N-gain 58.13% with sufficient criteria effective